Judicial Oversight on Annual Efficiency Reports in the State of Kuwait - Al-Kout, Amal (The Arab Journal of Administration, 2022)
The Judicial supervision of the legality of administrative procedures and decisions is considered an important guarantee, and one of the most important and effective forms of control and as a guarantee of individual rights and freedoms. The effectiveness and relevance of control are reflected in topics that are closely related to an employee’s life and career, in the exercise of his powers, he contacts the administrative authority, which, in its entirety, constitutes the idea of the presidential authority exercised by the authorities and administrative leadership over their staff at all levels of their jobs, This constitutes a risk of arbitrariness and delinquency in the use of such powers and in the face of which it is necessary to exercise all kinds of control over the administrative authority’s actions. Perhaps the Department’s best work is judicial control and political control that subject to political circumstances and considerations, and administrative control is not characterized by impartiality and Impersonality as self-censorship and cannot acknowledge its wrongdoing, thereby superior to judicial control and making it a claim of trust and independence. This study of judicial control of competency assessments was initiated, as efficiency assessments inevitably and directly affect the staff member’s material and moral promotions, so judicial decisions will be defined as a form of promotion that affects the prospects for obtaining and withholding such promotions. It is closely coupled with the public function. Therefore, legislation has consistently created legislative and legal protection for the public official, including the Kuwaiti legislator, by providing for judicial control of decisions on promotion. As a form of promotion, efficiency assessments are also subject to administrative and judicial hybrid surveillance, as this study will address in order to guarantee the employee’s rights and achieve justice.